A Simple Algorithm for Identifying the Direction of Arrows. Issue 5 (March 2019) - Xu, Yuhua; Liu, Jianghua; Xia, Cuicui; Zhou, Guopeng
Abstract: During the development of intelligent drive, the pursue for real-time and precise process of image has been the key point of research. This article introduces a simple way to identify the direction of arrows by means of their length and width.This method has been proven by Matlab.The Terasic's DE1-SoC development board and D5M camera are used to realize the algorithm. The result shows that this method has high performance on both timeliness and robustness.